Study on Palm Oil Kernel Shell Coarse Aggregate (PKSCA) as replacement material for coarse aggregate in concrete mix - Ahmad Jeni, Mohamad Luthfi; Zaini, Mohamad Azrul (Penerbit Uthm, 2018)
As we know the demand for material such as cement, fine and coarse aggregate is high. The construction industry is become bigger and bigger each day, but nowadays the price of material are not cheap like the old days. The price is increase drastically by 30% for the past few years. This condition is affecting the price of the construction process and the price of the building that will be sells. This also promotes fraud among the contractor which they may use the low quality material or changing the material specification in order to get more profits. So this study was carried out to find the alternative material for cement to overcome highly cost material especially coarse aggregate. This project aims were to reducing the usage of natural coarse aggregate in concrete mixture and to achieve most likely equivalent strength of normal concrete mixture.